Church Growth in Times of Secularization: A Case Study of People Joining Evangelical Congregations in the Netherlands - Vermeer, Paul (Review of religious research, 2021)
Background: Today the Dutch religious landscape is characterized by two opposite trends. On the one hand, there is a massive and dominant trend of religious disaffiliation which mostly affects the Roman Catholic Church and the mainline Protestant churches, while on the other hand the Netherlands also witnesses the emergence of several independent, evangelical congregations of near megachurch size. Purpose: Against the background of these opposite trends, this paper focuses on the second trend and tries to explain why some people join an evangelical congregation. Methods: For this purpose, quantitative data gathered among the audiences of six thriving evangelical congregations are analyzed in view of the following research questions: (1) What was the previous religious affiliation of the people who switched or converted to one of the six participating evangelical congregations? and (2) Which factors induced the switch or conversion to these congregations? Results: Results of bivariate and multivariate analyses show that these congregations attract both mainline and orthodox Protestant switchers as well as a significant number of secular converts, whose decision to join these evangelical congregations is induced by early socialization experiences, their intrinsic religious orientation and the switching of their partner. Closer scrutiny into the background of the apparent secular converts reveals, however, that several of these converts are probably re-affiliates. Although these secular converts indicated to be a religious none in their early teens, their conversion to evangelicalism is in part still induced by certain, early religious socialization experiences. Conclusions and Implications: This insight puts the alleged success of these evangelical congregations in more perspective. It shows that their success is more a matter of circulating, religious believers and not so much a matter of successfully reaching out to the unchurched. In all likelihood, then, thriving evangelical congregations will remain an exception in secular societies like the Netherlands and evangelical church growth in no way marks a break with the ongoing trend of religious disaffiliation.